Evaluating the effects of e-health interventions on mental health outcomes in individuals with breast cancer: A systematic review - Nurdiana Mohammad Hussin; Nik Ruzyanei Nik Jaafar; Idayu Badilla Idris; Azmawati Mohammed Nawi (PLoS ONE, 2025)
Individuals with breast cancer (BC) often experience significant psychological distress throughout their cancer journey, and while e-health interventions show promise, evidence of their effectiveness remains limited. This systematic review addresses this gap by evaluating the effects of e-health interventions on mental health outcomes among individuals with BC. This study followed PRISMA guidelines and was registered with PROSPERO (CRD42024543722). A comprehensive search was conducted from July to August 2024, using Scopus, Web of Science, and Ovid Medline databases. Studies were included if they: (1) applied experimental study designs, (2) implemented e-health interventions to improve mental health outcomes, and (3) focused specifically on individuals with BC. Two reviewers used Rayyan software and the predefined criteria for article exclusion and inclusion. Seven studies, predominantly from countries with high BC incidence rates and advanced healthcare systems, met the inclusion criteria. Thematic analysis revealed that e-health interventions improved psychological well-being, coping strategies, quality of life, physical health, and cancer-specific symptom management. However, diverse intervention designs and measurement tools hindered cross-study comparison. Many studies focused on general mental health measures, neglecting crucial aspects such as help-seeking behaviors, cognitive function, and concerns about cancer recurrence. Future research should standardize intervention protocols, ensure comprehensive outcome reporting, and expand mental health measures.